A15 VITAMIN D DEFICIENCY PROMOTES INTESTINAL AUTOPHAGY DYSFUNCTION VIA EPIGENETIC REGULATION INVOLVING MIR142-3P IN VITRO AND IN VIVO. (1st March 2018) - Bronte-Tinkew, D M; Dang, F; Hsieh, A; McGillis, L H; Verapalan, I; Murchie, R; Capurro, M; Greenfield, L K; Philpott, D; Jones, N
Abstract: Background: Growing evidence from animal and human studies indicate that vitamin D deficiency is an important environmental factor contributing to IBD pathogenesis. The exact mechanism underlying the role of vitamin D in IBD is currently unknown. Aims: We hypothesize that vitamin D deficiency reduces autophagy to promote IBD progression via a mechanism involving the upregulation of specific microRNAs. Methods: To address this hypothesis, C57BL/6 mice were fed either a vitamin D deficient or control chow diet for 5 weeks prior to extraction of the terminal ileum and colon for experimental analysis. Ileal whole tissue was analyzed via Western Blot for changes in autophagy proteins LC3-II and ATG16L1. To further explore this relationship between autophagy proteins and miRNA, bioinformatics target prediction tools were employed to identify miRNA predicted to target ATG16L1 3'UTR. A dual luciferase reporter assay was used to determine whether miR-142-3p directly targets ATG16L1 in intestinal cells. To characterize the functional effect of miR-142-3p, HTC-116 cells and intestinal organoids were transfected with either a miR mimic or the anti-miR. LC3-II and ATG16L1 levels from transfected cells were assessed by immunoblot. In addition, transfected cells were immunostained for LC3-II as a marker of autophagy. Expression of miR-142-3p in ileal whole tissue from vitamin D deficient animals was investigated via qPCR. Results: Ileal whole tissue homogenate from vitamin D deficient animals showed decreased levels of autophagy proteins ATG16L1 and LC3-II, indicating a role for vitamin D in promoting functional autophagy in vivo. Bioinformatics target prediction tools confirmed miR 142-3p as a target for ATG16L1. It was also selected for further characterization because of its known elevated expression in animal colitis models. Delivery of miR-142-3p mimic suppressed ATG16L1-3'UTR luciferase activity in HCT-116 cells. There was a reduction in both ATG16L1 and LC3-II protein levels in miR mimic transfected intestinal organoids and HTC-116 cells relative to control cells. In addition, a reduction in LC3 puncta characteristic of autophagosomes was detected in cells transfected with miR-142-3p mimic, when compared to sham-transfected cells. Furthermore, a significant upregulation of miR142-3p expression was detected in the ileum of vitamin D deficient animals as assessed by qPCR. Conclusions: These results indicate that miR142-3p can directly regulate ATG16L1 and repress autophagy. Ongoing studies are assessing the correlation between vitamin D deficiency and ileal mir 142-3p levels in a cohort of paediatric IBD patients. Taken together, our study demonstrates a potential mechanism by which vitamin D deficiency influences IBD pathogenesis. Funding Agencies: CAGCrohns and Colitis